Intersectionality in corporate South Africa: the experiences of African black female leaders - Mbatha, Siphiwe Wendy (Graduate School of Business (GSB), 2025)
Research on gender inequality focuses on the two main biases against women: (1) agentic deficiency (perceptions that women have minimal leadership potential); and (2) agentic penalty (a backlash against counter-stereotypical behaviour from certain women). There has generally been an assumption that the stereotypes upon which these biases are based are comparable for women across racial groups. South Africa, despite having significant racial and ethnic diversity, suffers from a lack of research that targets respondents by race and gender. This naïve gender-biased approach does not fully consider the critical intersectional differences that exist for women. In studies specific to South Africa, the lenses of both race and gender are often used to examine the perceptions of women as leaders. These views, which are limited to only gender and race, do not completely represent Black women, however, because gender intersections introduce simultaneous processes for identity and interdependent systems of disadvantage. These theories also do not elaborate on the lived experiences of South African Black women in corporate leadership roles. The researcher conducted a qualitative research study and interviewed 25 Black females who held various senior leadership positions in different industries in South Africa. The researcher applied a hermeneutic phenomenological approach to uncover the lived experiences of the group of respondents. The aim was to document their lived experiences and establish how those experiences related to constructs from existing literature on the leadership dynamics of race, gender, class, and intersectionality. The research findings capture the essence of the lived experiences of professional Black females and provide context as to why there continues to be a gap in the representation of this group in senior leadership positions, despite the efforts of affirmative action policies from the government. The findings highlight and demonstrate how this group is challenged and sometimes held back by the dynamics of intersectionality, class, race, gender, and other processes of identity. The research goes on to describe further research opportunities on how identity and interdependent systems of disadvantage impact Black female leadership performance over time. There is an opportunity to further explore how human resource policies and educational frameworks can contribute towards harnessing and developing this group, to increase their capacity and greater participation in senior- and executive-level roles.